Landscapes' capacities to provide ecosystem services - A concept for land-cover based assessments - Benjamin Burkhard; Franziska Kroll; Felix Müller; Wilhelm Windhorst (Landscape Online, 2009)
Landscapes differ in their capacities to provide ecosystem goods and services, which are the benefits humans obtain from nature. Structures and functions of ecosystems needed to sustain the provision of ecosystem services are altered by various human activities. In this paper, a concept for the assessment of multiple ecosystem services is proposed as a basis for discussion and further development of a respective evaluation instrument. Using quantitative and qualitative assessment data in combination with land cover and land use information originated from remote sensing and GIS, impacts of human activities can be evaluated. The results reveal typical patterns of different ecosystems' capacities to provide ecosystem services. The proposed approach thus delivers useful integrative information for environmental management and landscape planning, aiming at a sustainable use of services provided by nature. The research concept and methodological framework presented here for discussion have initially been applied in different case studies and shall be developed further to provide a useful tool for the quantification and spatial modelling of multiple ecosystem services in different landscapes. An exemplary application of the approach dealing with food provision in the Halle-Leipzig region in Germany is presented. It shows typical patterns of ecosystem service distribution around urban areas. As the approach is new and still rather general, there is great potential for improvement, especially with regard to a data-based quantification of the numerous hypotheses, which were formulated as base for the assessment. Moreover, the integration of more detailed landscape information on different scales will be needed in future in order to take the heterogeneous distribution of landscape properties and values into account. Therefore, the purpose of this paper is to foster critical discussions on the methodological development presented here.